A Survey of University Students' Preferences for Midwifery Care and Community Birth Options in 8 High‐Income Countries. (19th January 2020) - Stoll, Kathrin H.; Downe, Soo; Edmonds, Joyce; Gross, Mechthild M.; Malott, Anne; McAra‐Couper, Judith; Sadler, Michelle; Thomson, Gill; ,
Abstract : Introduction: Midwifery care is associated with positive birth outcomes, access to community birth options, and judicious use of interventions. The aim of this study was to characterize and compare maternity care preferences of university students across a range of maternity care systems and to explore whether preferences align with evidence‐based recommendations and options available. Methods: A cross‐sectional, web‐based survey was completed in 2014 and 2015 by a convenience sample of university students in 8 high‐income countries across 4 continents (N = 4569). In addition to describing preferences for midwifery care and community birth options across countries, this study examined sociodemographic characteristics, psychological factors, knowledge about pregnancy and birth, and sources of information that shaped students' attitudes toward birth in relation to preferences for midwifery care and community birth options. Results: Approximately half of the student respondents (48.2%) preferred midwifery‐led care for a healthy pregnancy; 9.5% would choose to give birth in a birthing center, and 4.5% preferred a home birth. Preference for midwifery care varied from 10.3% among women in the United States to 78.6% among women in the United Kingdom. Preferences for home birth varied from 0.3% among US women to 18.3% among Canadian women. Women, health science students, those with low childbirth fear, those who learned about pregnancy and birth from friends (compared with other sources, eg, the media), and those who responded from Europe were significantly more likely to prefer midwifery care and community birth. High confidence in knowledge of pregnancy and birth was linked to significantly higher odds of community birth preferences and midwifery care preferences. Discussion: It would be beneficial to integrate childbirth education into high school curricula to promote knowledge of midwifery care, pregnancy, and childbirth and to reduce fear among prospective parents. Community birth options need to be expanded to meet demand among the next generation of maternity service users.